KAJIAN MOTIF TENUN SONGKET MELAYU SIAK TRADISIONAL KHAS RIAU - Sasya Lestari; Menul Teguh Riyanti (Universitas Trisakti, 2017)
AbstractThe Analysis of Malay Siak Traditional Songket Weaving Motifs from Riau. Riau is one of the provinces in Indonesia that have Malay culture which still maintained and preserved until now. One of the cultures is the Malay Songket Weaving. Songketis from Siak and has a variety of motifs, colors and meanings that reflect way of life of the mankind. However, the times make people choose songket in terms of beauty, so the philosophy contained in songket is not considered. Songket is supposed to be the pride of Riau society, especially the younger generation which is expected to be the successor to the Malay culture. The lack of love for the culture and lack of adequate information makes the younger generation are less interested in this songket cloth. Knowledge on the meaning of motifs and colors on songket is needed so that Riau society and futuregenerations will not forget the philosophy that contained in the songket. The analysis of the traditional Melayu Siak weaving use descriptive qualitative method and source of references. Data collecting method is observation and interview. The result of thisanalysis is the knowledge of philosophy and value in the Melayu Riau weaving motifs.AbstrakKajian Motif Tenun Songket Melayu Siak Tradisional Khas Riau. Riau merupakan salah satu provinsi yang memiliki kebudayaan Melayu yang masih terjaga hingga sekarang. Salah satu dari kebudayaannya adalah Tenun Songket Melayu Riau. Kainsongket ini berasal dari Siak dan memiliki beragam motif, warna serta makna yang mencerminkan pandangan hidup umat manusia. Namun, perkembangan zaman membuat masyarakat memilih kain songket dari segi keindahan, sehingga falsafah yang terdapat dalam kain songket tidak lagi diperhatikan. Minimnya kecintaan akan budaya serta kurangnya informasi yang memadai membuat para generasi muda kurang tertarikakan kain songket ini. Pengetahuan akan makna dari motif serta warna pada kain songket diperlukan agar masyarakat Riau serta generasi penerusnya tidak melupakan falsafah yang terdapat didalamnya. Kajian motif tenun songket Melayu Siak tradisional ini dilakukan metode kualitatif deskriptif dengan menggunakan referensi kepustakaan. Pencarian data ditunjang dengan observasi dan wawancara. Hasil dari kajian ini adalahpemahaman terhadap falsafah dan nilai yang terkandung dalam motif tradisional tenun songket Melayu Riau tersebut.